Comparisons of functional movements and core muscle activity in women according to Pilates proficiency - Ko, Hyun Seo; Jung, Hyung-Ung; Park, Tae-Young; Song, Jong-Kook; Wang, Junsig; Jung, Hyun Chul (Frontiers in Physiology, 2024)
IntroductionThis study aims to investigate the differences in functional movements and core muscle activities between experienced and novice practitioners during Pilates exercises.MethodsThirty-eight participants were recruited for the study, comprising 19 experienced and 19 novice Pilates practitioners. Participants performed functional movement screening (FMS) tests and six Pilates exercises at the basic, intermediate, and advanced levels. Surface electromyography (EMG) was utilized to measure muscle activity at four sites: right rectus abdominis (RA), external oblique (EO), multifidus (MU), and longissimus (LO). Mean EMG activity, co-contraction indices, and duration of core muscle activation were analyzed using independent t-tests to examine the differences between groups. Cohen’s d was used to calculate effect sizes based on the standard deviations of the groups. Statistical significance was set at p < 0.05.ResultsThe experienced practitioners scored significantly higher in total FMS scores and in four sub-units of the FMS scores compared to the novice group (p ≤ 0.01). Mean EO EMG activity was also significantly greater in experienced practitioners during all Pilates exercises (p < 0.05). Additionally, the RA/EO co-contraction index was higher in experienced practitioners during the ‘double leg stretch’ exercise (p = 0.02).ConclusionThe results suggest that experienced Pilates practitioners have superior functional movement abilities and greater core muscle activation, particularly in the EO muscle group, compared to novice practitioners. These findings may assist Pilates instructors in refining instructional strategies to cater to different skill levels and enhance training effectiveness.